2019
DOI: 10.4236/aim.2019.91002
|View full text |Cite
|
Sign up to set email alerts
|

Xylooligosaccharides (XOS) as Emerging Prebiotics: Its Production from Lignocellulosic Material

Abstract: Prebiotics are non-digestible food supplements (oligosaccharides) which play an important role in stimulating the growth of beneficial bacteria especially Lactobacilli and Bifidobacteria in the colon of the host. Xylooligosaccharides (XOS) are more effective than other oligosaccharides such as fructo-oligosaccharides as dietary supplements. Chemical methods are preferred to produce XOS mixtures with a wide DP range, while enzymatic methods are preferred in the food or pharmaceutical industries to reduce format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Xylooligosaccharides (XOS) are non-digestible functional oligosaccharides with prebiotic activity, leading to their extensive use as food additives ( 1 ). As XOS exhibit excellent thermos-stability to 100°C and strong acid resistance across a pH range of 2.0–7.0, they are well-suited to gastrointestinal delivery given their ability to resist stomach acid ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Xylooligosaccharides (XOS) are non-digestible functional oligosaccharides with prebiotic activity, leading to their extensive use as food additives ( 1 ). As XOS exhibit excellent thermos-stability to 100°C and strong acid resistance across a pH range of 2.0–7.0, they are well-suited to gastrointestinal delivery given their ability to resist stomach acid ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, XOS can also directly develop health products and enhance the body's physique. According to clinical trials, XOS play an important role in treating diabetes, hypertension, hyperlipidemia, chronic hepatitis, irritable bowel syndrome, chronic gastroenteritis, osteoporosis, pruritus, and otitis ( 187 ). Sheu and other studies reported that 8 weeks of XOS as a dietary supplement could effectively improve blood glucose and lipid levels in type 2 diabetes ( 147 ).…”
Section: Application Of Xosmentioning
confidence: 99%
“…Hemicellulose, which is mainly composed of xylan, can be transformed to xylose, furfural, xylonic acid, xylitol, xylooligosaccharides (XOS) (Jayapal et al, 2013; Scopel and Rezende, 2021). Among others, XOS are acting as emerging functional oligosaccharides, which show favorable effects on human intestinal ora by selectively promoting the growth of probiotic bacteria (Lian et al, 2020;Mhetras et al, 2019). The worldwide market for XOS is increasing yearly, and it is estimated to reach $ 130 million by 2023, which makes XOS become one of the most competitive products all over the world (Santibáez et al, 2020;Singh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%